Cactus City / Nurjeha Ramli - Ramli, Nurjeha (2021)
Cactus City is a cute gift that sell mini cactus and cute succulents. The main objective that is to achieve for the business is to offer the cute mini cactus and cute succulent as a gift at a better price, affordable price and quality than other retailer. This business began on Facebook on 5 6 th June 2020, humbly beginning with three collections and steadily adding more from our business journey. The highest quality and the competitive prices of this commodity are well known to many. This product therefore offers a clear analysis of our customers continued purchases. Since commencement, Cactus Mini was sold more than 50 mini cactus and succulents with different types of size of pot. Next, Cactus City has made over 15 sales and the numbers are expecting to grow the end of the year through Year End sale. Increasing demands for our product results into a good profitable sale revenue to our business project. By the end of year, we now have collections made for our customers and also cute new design of succulents in a beautiful pot as a gift.